Evaluating mercury concentrations in edible plant and fungi species in the Canadian Arctic environment. Issue 4 (24th June 2021) - Bergin, Ryan; Koch, Iris; Rutter, Allison; Shirley, Jamal; Zeeb, Barbara
Abstract: Levels of environmental mercury (Hg) within the Canadian Arctic are a current area of concern. Although efforts have been made to reduce Hg released into the environment, levels remain elevated in flora and fauna. This study examined the concentrations of Hg in soil and naturally occurring edible plant and fungi species, identified by local Inuit residents, from eight locations in Iqaluit, Nunavut, and the surrounding area during the summers of 2018 and 2019. Total Hg concentrations were obtained in 24 soil samples, 112 flora samples from 23 plant and five lichen species, and 157 fungal samples from eight species. Median Hg concentrations in plant species ranged from 0.005 μg g −1 Hg dry weight (dw) in Saxifraga cernua to 0.19 μg g −1 Hg dw in Oxytropis maydelliana . Median concentrations in edible fungi species ranged from 0.084 μg g −1 Hg dw in the Cortinarius croceus (non‐puffball species) to 1.6 μg g −1 Hg dw in Lycoperdon perlatum (a puffball mushroom). Additionally, median Hg concentration in puffball species (1.4 μg g −1 ) were higher than non‐puffball species (0.12 μg g −1 ). Three puffball species were assessed for methylmercury (MeHg), with mean concentrations ranging from 0.013 to 0.085 μg g −1 MeHg dw. Limited research has been conducted on Hg uptake in naturally occurring edible plant and fungi species of the Canadian Arctic. This study contributes important information on Hg accumulation and processes in edible plant and fungi Arctic species, is the first to focus on plants used by the local Indigenous community, and demonstrates a need for further studies to assess Hg in Arctic environments. Core Ideas: Mercury in the Canadian Arctic is at elevated concentrations in soils, plants, and fungi. Mercury levels in soils and 23 plant, five lichen, and eight fungal species were assessed. Levels of mercury in soils across locations were not statistically different. Concentrations ranged from 0.005 μg g −1 Hg dw in S. cernua to 1.6 μg g −1 Hg dw in L. perlatum . Fungi showed higher levels of mercury compared with plants, in particular puffballs.